Causes of Delayed Hospitalization In Periampullary Carcinoma and Its Correlation With Perioperative Outcome (Journal of Dhaka Medical College, 2016)
Abstract not availableJ Dhaka Medical College, Vol. 24, No.1, April, 2015, Page 17-23